Genetic landscape of patients with ALK-rearranged non-small-cell lung cancer (NSCLC) and response to ceritinib in ASCEND-1 study - Tan, Daniel S.-W.; Thomas, Michael; Kim, D-W.; Szpakowski, S.; Urban, P.; Mehra, R.; Chow, L. Q. M.; Sharma, S.; Solomon, B. J.; Felip, E.; Camidge, D. R.; Vansteenkiste, J.; et al. (Lung cancer, 2022)
Objectives - To better understand genetic determinants of response to ceritinib, an exploratory analysis was conducted using tumor biopsies from anaplastic lymphoma kinase (ALK)-rearranged (ALK+) non-small-cell lung cancer (NSCLC) patients treated with ceritinib at doses of ≥ 300 mg in the ASCEND-1 study. - Methods - ASCEND-1 was an open-label, multicentre, phase 1, dose-escalation and expansion study of ceritinib (fasted) in ALK inhibitor (ALKi)-naïve or ALKi-pretreated patients with locally advanced or metastatic ALK + NSCLC. Biopsies were assayed by next-generation sequencing (NGS) using a Foundation Medicine panel targeting 295 genes. Somatic alterations were correlated with clinical outcome (cut-off 14-Apr-2014). A total of 285 ALK + NSCLC patients were treated with ceritinib at doses ≥ 300 mg. - Results - NGS data were generated for 85 pts (ALKi-pretreated [n = 54]; ALKi-naïve [n = 31]), 57 were collected from patients before exposure to any ALKi. NGS did not detect ALK rearrangement in 14 of 85 patients; several of these ALK NGS negative cases harbored alternative drivers, e.g. EGFR mutation. Of the 71 biopsies with NGS confirmed ALK rearrangement, the most frequently detected rearrangements were EML4-ALK variant 1 (V1) and EML4-ALK V3 (36.6% [26/71] and 32.4% [23/71] respectively). Eight (six crizotinib-pretreated and two pretreated with crizotinib followed by alectinib) of the 21 ALKi-pretreated patients carried a point mutation of the ALK TKD, and had the biopsy collected between 1 and 14 days before ceritinib; with the exception of one patient with a G1202R point mutation, all patients derived clinical benefit from ceritinib treatment. Of the 14 ALKi-naïve patients, ceritinib was effective in almost all patients, including a patient carrying a concomitant ERBB4 and HGF amplification. - Conclusions - This exploratory analysis highlights the potential role of NGS in improving our understanding of response and resistance to ceritinib. It also illustrates that ceritinib is active against almost all ALK resistance mutations found in ALKi-pretreated patients. Trial registration: ClinicalTrials.gov, NCT01283516. Registered January 26, 2011, https://clinicaltrials.gov/ct2/show/NCT01283516